Acute forearm compartment syndrome in a newborn caused by reperfusion after spontaneous axillary artery thrombosis. Issue 6 (November 2015) - Bekmez, Senol; Beken, Serdar; Mermerkaya, Musa Ugur; Ozkan, Mehpare; Okumus, Nurullah
Abstract : Acute compartment syndrome of the forearm in newborns is often misdiagnosed and can be disastrous if left untreated. Here, we report a full-term infant of a diabetic mother with underlying heterozygosity for MTHFR C677T and A1298C alleles. A spontaneous thrombosis occurred in the left axillary artery immediately after birth. The patient responded well to anticoagulant (heparin) and thrombolytic (tissue plasminogen activator) agents. After reperfusion of the extremity, acute compartment syndrome developed. Emergent fasciotomy was performed. In this case, effective collaboration between pediatricians and orthopedic surgeons resulted in salvage of the extremity, with good clinical and functional results.